Hubungan Pemberian Cairan Preloading Dengan Peningkatan Tekanan Darah Pada Pasien Yang Menjalani Anestesi Spinal - Rahayu Setyaningsih (Barongko: Jurnal Ilmu Kesehatan, 2026)
Spinal anesthesia is a regional anesthetic technique widely used in surgical procedures, but it often causes side effects in the form of hypotension due to sympathetic blockade. One way to prevent hypotension is by administering preloading fluids before spinal anesthesia. This study aimed to determine the relationship between preloading fluid administration and increased blood pressure in patients undergoing spinal anesthesia. This study used a quantitative analytical design with a cross-sectional approach. The study sample consisted of 60 patients undergoing spinal anesthesia and was selected using a purposive sampling technique. Data were collected through observations of preloading fluid administration and blood pressure measurements before and after spinal anesthesia. Data analysis was performed using the Chi-Square test. The results showed a significant relationship between preloading fluid administration and increased blood pressure in spinal anesthesia patients with a p-value <0.05. It was concluded that preloading fluid administration is associated with stability and increased blood pressure in patients undergoing spinal anesthesia.